2021
DOI: 10.3389/fgene.2021.784545
|View full text |Cite
|
Sign up to set email alerts
|

Programmed Degradation of Pericarp Cells in Wheat Grains Depends on Autophagy

Abstract: Wheat is one of the most important food crops in the world, with development of the grains directly determining yield and quality. Understanding grain development and the underlying regulatory mechanisms is therefore essential in improving the yield and quality of wheat. In this study, the developmental characteristics of the pericarp was examined in developing wheat grains of the new variety Jimai 70. As a result, pericarp thickness was found to be thinnest in grains at the top of the spike, followed by those… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…The copyright holder for this preprint this version posted June 3, 2024. ; https://doi.org/10.1101/2024.06.02.596756 doi: bioRxiv preprint showed high expression in the pericarp at 4 dap, influencing grain size by regulating the rate of pericarp degradation (Li et al, 2021). PHS was robust expressed at 8 dap and 12 dap in the central endosperm and prismatic cells, which indicates the spatiotemporal specific expression of PHS1 is crucial for the initiation of B-type granules (Kamble et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The copyright holder for this preprint this version posted June 3, 2024. ; https://doi.org/10.1101/2024.06.02.596756 doi: bioRxiv preprint showed high expression in the pericarp at 4 dap, influencing grain size by regulating the rate of pericarp degradation (Li et al, 2021). PHS was robust expressed at 8 dap and 12 dap in the central endosperm and prismatic cells, which indicates the spatiotemporal specific expression of PHS1 is crucial for the initiation of B-type granules (Kamble et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Previously reported genes involved in grain size regulation and grain quality were found to exhibit cell type-specific expression in our spatial data. For instance, ATG8a showed high expression in the pericarp at 4 dap, influencing grain size by regulating the rate of pericarp degradation (Li et al, 2021). PHS was robust expressed at 8 dap and 12 dap in the central endosperm and prismatic cells, which indicates the spatiotemporal specific expression of PHS1 is crucial for the initiation of B-type granules (Kamble et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…In seed development of wheat and barley, the pericarp degenerates to provide space and remobilize nutrients to the developing seeds. The dead cells in the pericarp collapse and reduce to several layers of cuticles, serving as a protectant to the embryo ( Domínguez and Cejudo 2014 ; Li et al 2021 ). Our results suggest a similar scenario in E. tef and probably other Eragrostis species.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, it has previously been shown that γVPE can be translocated through ER bodies ( Figure 3 ) to the vacuole to promote stress-induced cell death in young seedlings of Arabidopsis thaliana [ 95 , 96 ]. Nevertheless, it has also been found that dPCD of pericarp cells in wheat ( Triticum ) grains coexists with the autophagy pathway, as silencing Atg8 inhibited dPCD and caused the formation of small premature grains with a thick pericarp layer [ 97 ]. However, by the manipulation of autophagy with inhibitors and accelerants such as concanamycin A, wortmannin, and rapamycin, autophagy was found to promote cell survival rather than cell death in the lace plant ( Aponogeton madagascariensis ).…”
Section: Autophagy Contribution To Cell Deathmentioning
confidence: 99%